Microstructural Evolution of Plasma-Sprayed Cast Iron Coatings at Different Deposition Temperatures and Its Effect on Corrosion Resistance - Xing, Ya-Zhe; Wang, Ke; Feng, Xiao; Wei, Qiu-Lan; Chen, Yong-Nan (Journal of thermal spray technology, 2019)
The properties of a thermally sprayed coating are primarily determined by the porosity and inter-lamellar bonding. In this work, three cast iron coatings were prepared by the atmospheric plasma spraying process. In the spraying process, the surface temperatures (deposition temperatures) of the coatings were controlled to be 50 ± 5, 180 ± 6, and 240 ± 8 °C. The microstructures of the coatings were characterized by field emission scanning electron microscopy. Both electrochemical polarization and immersion tests in 0.5 mol/L sulfuric acid solution were employed to evaluate the influence of deposition temperature on the corrosion behavior of the coatings. The results of these tests indicated that the coating deposited at high temperature shows a higher corrosion resistance than the coating deposited at low temperature, which was attributed to the reduced porosity of the coating resulting from the improvements in the flattening of the molten particles and the bonding between lamellae with raising the deposition temperature.